Gọi biểu thức trên là A. Ta có:
A = 2 + ( 2+ 1).4 + ( 4 + 1)6 + … + (98 + 1).100
= 2 + 2.4 + 4 + 4.6 + 6 + … + 98.100 + 100
= (2.4 + 4.6 + … + 98.100 ) + (2 + 4 + 6 + … + 100)
= 98.100.102 : 6 + 102.50:2
= 166600 + 2550
= 169150
Gọi biểu thức trên là A, ta có :
A = 1x2 + 2x3 + 3x4 + 4x5 + ...+ 99x100
A x 3 = 1x2x3 + 2x3x3 + 3x4x3 + 4x5x3 + ... + 99x100x3
A x 3 = 1x2x3 + 2x3x(4-1) + 3x4x(5-2) + 4x5x(6-3) + ... + 99x100x(101-98)
A x 3 = 1x2x3 + 2x3x4 - 1x2x3 + 3x4x5 - 2x3x4 + 4x5x6 - 3x4x5 + ... + 99x100x101 - 98x99x100.
A x 3 = 99x100x101
A = 99x100x101 : 3
A = 333300